Single-shrine temple built in the Latina (mono-spire) style of temple architecture - Temples of India Project Team (Jio Institute, 2024)
Seen here is the west-facing back elevation of the southern shrine from the Triple Shrine Temple in the Mahanaleshwar temple cluster. This is a single-shrine temple built in the latina (mono-spire) style of temple architecture. Only two levels of the shikhara (superstructure) are in situ. Other architectural fragments of the temple are found in the vicinity. Except for the bhadra projection, the temple does not have any sculptures on the exterior wall surfaces. The ornamentation of the temple mainly consists of geometric patterns, floral motifs, and architectural decorations.